복합유역의 침수해석을 위한 이중배수체계 유출모형의 적용 - 이재준; 곽창재; 이성호; Lee, Jaejoon; Kwak, Changjae; Lee, Sungho (Journal of Korea Water Resources Association, 2019)
The importance of the dual drainage system model has increased as the urban flood damage has increased due to the increase of local storm due to climate change. The dual drainage model is a model for more accurately expressing the phenomena of surface flow and conduit flow. Surface runoff and pipe runoff are analyzed through the respective equations and parameters. And the results are expressed visually in various ways. Therefore, inundation analysis results of dual drainage model are used as important data for urban flood prevention plan. In this study, the applicability of the COBRA model, which can be interpreted by combining the dual drainage system with the natural watershed and the urban watershed, was investigated. And the results were compared with other dual drainage models (XP-SWMM, UFAM) to determine suitability of the results. For the same watershed, the XP-SWMM simulates the flooding characteristics of 3 types of dual drainage system model and the internal flooding characteristics due to the lack of capacity of the conduit. UFAM showed the lowest inundation analysis results compared with the other models according to characteristics of consideration of street inlet. COBRA showed the general result that the flooded area and the maximum flooding depth are proportional to the increase in rainfall. It is considered that the COBRA model is good in terms of the stability of the model considering the characteristics of the model to simulate the effective rainfall according to the soil conditions and the realistic appearance of the flooding due to the surface reservoir. 기후 변화로 인한 국지성 호우의 증가로 도시의 내수침수피해가 증가함에 따라 이중배수체계 모형의 중요성이 증가하였다. 이중배수체계 모형은 지표면의 흐름과 관거의 흐름의 현상을 보다 정확히 표현하기 위하여 표면유출과 관거 유출을 각각의 관련 방정식과 매개변수들을 통해 해석하며, 이를 시각별로 연동하여 동시에 시뮬레이션하는 모형으로 이중배수체계 모형의 침수해석 결과는 도시계획 및 침수예방을 위한 계획 수립시 중요한 자료로 사용되고 있다. 본 연구에서는 자연유역과 도시유역이 혼재되어 있는 복합유역에 이중배수체계를 접목하여 해석이 가능한 COBRA 모형을 실제 유역에 적용하여 그 적용성을 파악해 보고 다른 이중배수체계 모형인 XP-SWMM, UFAM과 비교하여 결과의 적합성을 판단해 보았다. 동일한 대상유역에 대해 3가지 형태의 이중배수체계 모형의 침수해석 결과 및 침수양상을 분석한 결과를 종합해볼 때 우수관망의 용량 부족으로 발생하는 내수침수 특징은 XP-SWMM이 비교적 잘 모의하는 것으로 보였으며, UFAM은 도로의 빗물받이를 고려하는 특징에 따라 타 모형에 비해 가장 낮은 침수해석 결과를 나타내었다. 마지막으로 COBRA는 침수면적과 침수면적의 비율, 최대침수심이 강우량 증가에 비례하는 일반적인 결과와 토양조건에 따라 유효우량을 세밀하게 분류하여 모의하는 모형 특성 및 지표 저류에 의한 침수양상이 나타나는 현실성을 고려할 때 모형의 안정성 측면에서 양호하다고 판단되었다.